EXAMINING SENSORY MARKETING AND BRAND EXPERIENCE INFLUENCE ON BRAND LOYALTY IN EAST JAVA LUXURY RETAIL - Feishya Mitzvella; Charly Hongdiyanto (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
The growth of the luxury goods market in Indonesia has increased the importance of experience-based marketing strategies, particularly through sensory marketing and brand experience. This study aims to analyze the influence of sensory marketing and brand experience on emotional attachment and their implications for brand loyalty among luxury product consumers in East Java. Using a quantitative correlational method with 160 respondents selected through purposive sampling, the data were analyzed using SEM-PLS. The results indicate that both sensory marketing and brand experience have a positive and significant effect on emotional attachment. Emotional attachment also significantly influences brand loyalty. Meanwhile, sensory marketing shows no direct effect on brand loyalty, whereas brand experience demonstrates a significant direct influence. Mediation analysis reveals that emotional attachment fully mediates the relationship between sensory marketing and brand loyalty, and partially mediates the relationship between brand experience and brand loyalty. These findings highlight that multisensory and experiential brand strategies strengthen consumers’ emotional bonds, ultimately enhancing brand loyalty. The study offers practical implications for luxury retailers in East Java to optimize customer experience through multisensory engagement to maintain loyalty in an increasingly competitive market.